Influence of ai chatbot communication features and ai service agent marketing effort on customer satisfaction in online car rental platform - Muslim, Aini Khalida; Kok, Hao Yuan; Mohd Tan, Athirah; Ishak, Muhamad Izaidi; Ahmad, Naveed; Govinda Raj, Vimala (Research and Scientific Innovation Society, 2026)
This paper discusses how AI chatbot communication features and AI service agent marketing activities affect customer satisfaction in online car rental websites in Malaysia, as a response to the industry deterioration due to the inability to access customer support, complicated booking processes, and the obsolete systems. Based on the service, quality measurement (SERVQUAL) model, the research is centered on the responsiveness and emotional expression of AI chatbots, the interaction and problem-solving ability of AI service agents, as important factors of customer satisfaction. A cross-sectional research design that was quantitative was adopted, and the data was gathered using an online survey with a convenience sample of 384 Malaysian users above the age of 18 years with prior experience of interacting with AI chatbots on online car rental sites. ANOVA was used to analyse the observed data through SPSS version 27.0. The results indicate that the features of chatbots communication with customers and marketing activities by the AI service agents positively influence customer satisfaction significantly, which is why the combination of an efficient and emotionally responsive AI communication with efficient service interaction and problem-solving is essential. The findings indicate that the properly developed AI chatbots can increase the rate of service and user experience, whereas marketing-oriented AI service agents can further improve customer trust and satisfaction. Future studies are advised to use methodologies of longitudinal studies, use of probability sampling and cross industry or cross-country comparisons. In practice, the research suggests that online car rental services and tourism-related companies should invest in emotionally intelligent and responsive AI chatbot systems with strong AI-assisted service agent abilities that would enhance customer satisfaction and maintain competitiveness.